An Empirical Model of Collective Household Labour Supply with Nonparticipation - Hans G. Bloemen (Tinbergen Institute, 2004)
We present a structural empirical model of collective household labour supply.Following recent developments in the literature on collective household labour sup-ply our model allows for the nonparticipation decision, along with the choiceof working hours. We use the theoretical framework for the specification of a simul-taneous model for hours, participation and wages of husband and wife. We discussthe problems of identification and statistical coherency that arise in the applicationof the collective household labour supply model. The model is estimated using apaneldata set of Dutch couples. The paneldata allow for the inclusion of randomeffects. The estimates allow us to check the underlying regularity conditions onindividual preferences, and to obtain estimates of the sharing rule that governs thedivision of household income between husband and wife.
Keywords: J64; 330; Labour supply; Household behaviour; Collective model; Arbeitsangebot; Haushaltsökonomik; Privater Haushalt; Schätzung; Niederlande